2005
DOI: 10.1177/0165551505049262
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of virtual libraries in Nigeria: myth or reality?

Abstract: The article investigates factors that may make the Nigeria Virtual Library Project a myth or reality. Questionnaires were used for data collection, using 22 University Librarians in federal universities as respondents, and 14 (64%) University Librarians completed the questionnaires. Three indicators were used to determine the myth or reality of evolving virtual libraries in Nigeria: availability of information infrastructures, human capacity building programmes in ICT, and level of funding of university librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…The likelihood that the development and provision of EIRS and services may be witnessing some improvement over the years can plausibly account for observed increased duration of usage. Related studies (Womboh and Abba, 2008; Etim, 2006;Ani, et al, 2005) had reported series of efforts made by academic libraries in Nigeria to adopt technologies for improved information access, citing such constraints like erratic internet access, unstable power supply, inadequate infrastructure, human resource deficit and low level technological and literacy skills among others. In the same vein, researchers are discussing how these various challenges are being tackled so that Nigerian university libraries can benefit from e-library initiatives, especially resource sharing due to the variety of electronic/digital formats and platforms available.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood that the development and provision of EIRS and services may be witnessing some improvement over the years can plausibly account for observed increased duration of usage. Related studies (Womboh and Abba, 2008; Etim, 2006;Ani, et al, 2005) had reported series of efforts made by academic libraries in Nigeria to adopt technologies for improved information access, citing such constraints like erratic internet access, unstable power supply, inadequate infrastructure, human resource deficit and low level technological and literacy skills among others. In the same vein, researchers are discussing how these various challenges are being tackled so that Nigerian university libraries can benefit from e-library initiatives, especially resource sharing due to the variety of electronic/digital formats and platforms available.…”
Section: Discussionmentioning
confidence: 99%
“…In University libraries, there are numerous library users including undergraduate students who need information for project writing. The students need information for their studies and research (Ani, 2005& Ugbagir, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, to create easy accessibility of library resources to library users in the universities, National Universities Commission of Nigeria established rules and regulations that faculty libraries should be established to decentralize university resources and sitting capacity. In order to abide by these rules and regulations, during the rule of Professor Akase Sorkar as the Vice Chancellor of Benue State University in the year 2006, five (5), more faculty libraries were established besides that of Faculty of Law and Health Sciences which are unique in nature. The aim and objectives of establishing faculty libraries was to equip them with specific library resources that tally with the programs offered in that faculty, as well as bringing the library closer to the faculty members.…”
Section: Introductionmentioning
confidence: 99%
“…ICTs are the principal agent and infrastructure of globalization. The importance of information infrastructures and networks such as local area networks (LANs), virtual libraries and other virtual structures (Ani, 2005) in accelerating the globalization of library services and the attendant transformation of library practices in the country cannot be overemphasized. Through these IT infrastructures and networks, there exists a new and higher level of communication and cooperation among different libraries in Nigeria.…”
Section: Introductionmentioning
confidence: 99%